Amenore Sekunder - Shariff, Fonda Octarianingsih; Rizdanti, Fezagustia (Medula, 2024)
Primary amenorrhea is a condition where menstruation does not occur in women aged 16 years. This situation occurs in women of reproductive age 0.1-2.5%. Meanwhile, secondary amenorrhea is the absence of menstruation for three cycles or 6 cycles after previously having a normal menstrual cycle. The incidence rate is around 1 to 5% in women of reproductive age. Treatment or management of amenorrhea depends on the cause. If the cause is drastic weight loss or obesity, sufferers are advised to follow an appropriate diet. If the cause is excessive exercise, sufferers are advised to reduce it. If the cause is a tumor, then surgery is performed to remove the tumor. So basically treating amenorrhoea always requires the help of a doctor to help diagnose or find the cause. The patient came to the Pertamina Bintang Amin Husada Hospital polyclinic on February 6 2024 with complaints of no menstruation since 4 months accompanied by lower abdominal and back pain. The treatment obtained by the patient was observation of bleeding, checking vital signs regularly, norelut tab twice a day, 2 tablets for 5 days, the patient was advised to diet. The prognosis for this patient is dubia ad bonam. The working diagnosis in this case is secondary amenorrhea based on clinical considerations, physical examination findings, and supporting examinations.